Alloy Engineering in Few‐Layer Manganese Phosphorus Trichalcogenides for Surface‐Enhanced Raman Scattering. (3rd February 2020) - Hou, Xiangyu; Zhang, Xuyang; Ma, Qingwei; Tang, Xiao; Hao, Qi; Cheng, Yingchun; Qiu, Teng
Abstract: Manganese phosphorus trichalcogenides are widely used in the field of photocatalysis and magnetic studies due to their broadband gaps. Herein, an alloy engineering method for the few‐layer manganese phosphorus trichalcogenides (MnPS3– x Se x, 0 ≤ x ≤ 3) in surface‐enhanced Raman scattering (SERS) is reported. A new strategy, with the coupling of exciton resonance ( µ ex ) and photoinduced charge transfer (PICT), is applied to screen out materials for SERS enhancement. According to the calculation of density functional theory, the bandgap of manganese phosphorus trichalcogenides (MnPS3 ) can be adjusted to match the band energy of Rhodamine 6G molecules by alloy engineering. Furthermore, a series of few‐layer MnPS3– x Se x (0 ≤ x ≤ 3) are fabricated to study the PICT‐induced SERS behavior under resonance excitation. The good performance with a detection limit down to 10 −9 m indicates that the synergistic resonances between µ ex and PICT are crucial to the enhancement. Abstract : Alloy engineering fabricating few‐layer MnPS3, MnPS2.4 Se0.6, MnPS1.8 Se1.2, MnPS1.2 Se1.8, MnPS0.6 Se2.4 and MnPSe3 for SERS measurement is predicted by a µ ex process. All samples could be used to probe the signal of R6G at a detection limit of 10 −9 m on few‐layer MnPS2.4 Se0.6 . More SERS‐active materials are expected to be discovered by the µ ex process.